Technological Change and Domestic Outsourcing - Bergeaud, Antonin; Malgouyres, Clément; Mazet-Sonilhac, Clément; Signorelli, Sara (Journal of Labor Economics, 2025)
Domestic outsourcing has grown substantially in developed countries over the past two decades. This paper addresses the question of the technological drivers of this phenomenon by studying the impact of the staggered diffusion of broadband internet in France during the 2000s. Our results confirm that broadband technology increases firm productivity and the relative demand for high-skill workers. Further, we show that broadband internet led firms to outsource some non-core occupations to service contractors, both in the low and high-skill segments. In both cases, we find that employment related to these occupations became increasingly concentrated in firms specializing in these activities, and was less likely to be performed in-house within firms specialized in other activities. As a result, after the arrival of broadband internet, establishments become increasingly homogeneous in their occupational composition. Finally, we provide suggestive evidence that high-skill workers experience salary gains from being outsourced, while low-skill workers lose out.